Pemodelan Sosial Kesehatan pada Usia Lanjut (Lansia) di Kota Palopo - Rasyid, Djusmadi; Rante, Anshar (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The composition of the elderly population is growing rapidly in both developed and developing countries, this is due to a decrease in fertility (birth) and mortality (death), as well as an increase in life expectancy (life expectancy). The aging process or the elderly experience prores regression or degeneration. Thus, the elderly are categorized as non-productive age, so that they become a burden or Dependency Ratio. The social fact is, many elderly people are still active in meeting their needs or living their lives by doing various kinds of activities and or jobs such as cleaning the yard, selling in the market, working in rice fields, gardens, ponds and other activities that exist in the community. Macro overview, related to the increase in the elderly population in Indonesia that can cause problems, especially in the medical, psychological, economic, and social aspects. This situation certainly requires serious attention and efforts to improve public services, especially for physical and / or health problems of the elderly.